Antibacterial profile of Jatropha curcas latex extracts against selected human pathogenic bacteria - Suhaili, Zarizal; Yeo, Chew Chieng; Yasin, Hasrif Nurhana; Badaludin, Nor Afiza; Zakaria, Zainul Amiruddin (Academic Journals, 2011)
Jatropha curcas is a drought-resistant tree belonging to the family Euphorbiaceae. The latex of J. curcas has been traditionally used to heal wounds and has reported anti-coagulant and coagulant properties. In this study, fractions of the methanol, aqueous, ethyl acetate and hexane extracts from the Jatropha latex were tested for antibacterial properties against nine different human pathogenic bacteria, namely three different isolates of Staphylococcus aureus (one methicillin-resistant strain MRSA ATCC 33591, and two methicillin-sensitive strains MSSA ATCC 29213 and ATCC 25174), Salmonella enterica serovar typhi, Streptococcus agalactiae, Serratia marcescens, Klebsiella pneumoniae, Enterococcus faecalis (E248), Escherichia coli (ATCC 35218), Listeria monocytogenes (IMR L10), and Morganella morgenii (IMR MM99). The zones of inhibition produced by the extracts using an agar well diffusion method against the test microorganisms were found to range from 2.7 to 29 mm. The methanol extract was found to be the most effective extract with MIC values ranging from 0.39 mg/ml for methicillin-sensitive S. aureus and 6.25 mg/ml for S. marcescens. Hexane extracts did not show any antibacterial activity. Phytochemical screening of the J. curcas latex indicated the presence of saponins and tannins which are known to have antibacterial properties.